MOC Doped with Graphene Nanoplatelets: The Influence of the Mixture Preparation Technology on its Properties - Martina Záleská (Materials, 2021)
The ongoing tendency to create environmentally friendly building materials is nowadays connected with the use of reactive magnesia-based composites. The aim of the presented research was to develop an ecologically sustainable composite material based on MOC (magnesium oxychloride cement) with excellent mechanical, chemical, and physical properties. The effect of the preparation procedure of MOC pastes doped with graphene nanoplatelets on their fresh and hardened properties was researched. One-step and two-step homogenization techniques were proposed as prospective tools for the production of MOC-based composites of advanced parameters. The conducted experiments and analyses covered X-ray fluorescence, scanning electron microscopy, energy-dispersive spectroscopy, high-resolution transmission electron microscopy, sorption analysis, X-ray diffraction, and optical microscopy. The viscosity of the fresh mixtures was monitored using a rotational viscometer. For the hardened composites, macro- and micro-structural parameters were measured together with the mechanical parameters. These tests were performed after 7 days and 14 days. The use of a carbon-based nanoadditive led to a significant drop in porosity, thus densifying the MOC matrix. Accordingly, the mechanical resistance was greatly improved by graphene nanoplatelets. The two-step homogenization procedure positively affected all researched functional parameters of the developed composites (e.g., the compressive strength increase of approximately 54% after 7 days, and 37% after 14 days, respectively) and can be recommended for the preparation of advanced functional materials reinforced with graphene.